2011
DOI: 10.2478/s11532-011-0134-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of heavy metals from wastewater using micellar enhanced ultrafiltration technique: a review

Abstract: Application of Micellar enhanced ultrafiltration (MEUF) for the removal of different heavy metals has been reviewed. It is considered an economical alternative available to the conventional membrane separation process, because it reduces the requirement of higher pressure and high membrane costs. MEUF is a separation processes which uses surfactants and ultrafiltration membranes to remove multivalent ions from wastewater with high percent rejection using electrostatic attraction between metals and micelles.Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 104 publications
0
32
0
3
Order By: Relevance
“…The increasing problem of inorganic pollution of water, mainly with heavy metals, has caused great interest in technological methods enabling the removal of these compounds. Commonly used methods are precipitation (Lewis 2010), membrane techniques (Mungray et al 2012), ion exchange (Maturana et al 2011), extraction (Regel-Rosocka et al 2006), and adsorption (Chen et al 2012); see Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing problem of inorganic pollution of water, mainly with heavy metals, has caused great interest in technological methods enabling the removal of these compounds. Commonly used methods are precipitation (Lewis 2010), membrane techniques (Mungray et al 2012), ion exchange (Maturana et al 2011), extraction (Regel-Rosocka et al 2006), and adsorption (Chen et al 2012); see Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…However, besides surfactant concentration and nature, operating parameters, like transmembrane pressure, process temperature, metal ion concentration, feed flow rate, pH value, and operating time, have to be investigated to optimize the process, as reported in recent reviews (Bade and Lee 2011;Mungray et al 2012). …”
Section: Introductionmentioning
confidence: 98%
“…Cobalt in traces favors red blood cell production, but it is a toxic metal if ingested in high concentrations (Karate and Marathe 2008). In a recent review (Mungray et al 2012), the discharge limit of various heavy metals were reported, together with their potential health effects and common sources, stated by EPA in 1994(CFR 1994.…”
Section: Introductionmentioning
confidence: 98%
“…Among many technologies, which enable the removal of impurities from aqueous solutions, adsorption (Du et al 2011;Salam and Burk 2010;Zheng et al 2009), ion exchange, photocatalysis, filtration, coagulation, chemical precipitation, and electrodialysis or reverse osmosis (Chen et al 2012;Gupta et al 2012a, b, c;Maturana et al 2011;Mungray et al 2012), can be mentioned. Nonetheless, it is the adsorption process that provides scientists with a full spectrum of possibilities, in view of the wide range of available adsorbents supplied by nature (''natural adsorbents'') and waste materials both known as low-cost adsorbents (Gupta and Nayak 2012;Jain et al 2003;Mittal et al 2009aMittal et al , b, 2010a.…”
Section: Introductionmentioning
confidence: 99%